Livestock and poultry genetic resources of Manipur: status, distribution and types - Rahul Behl,; Reena Arora,; Sonika Ahlawat,; PK Vij, (Journal of Livestock Biodiversity, 2025)
Manipur is a small state in the North-Eastern region of India. Although the total livestock population of the Manipur constitutes only 0.136 percent of our country, the number of animals per household (1.48) is comparable to the national average (1.95). The number of backyard birds per household (5.16) is more than six times than the national average (0.83). Manipur is also home to Manipuri pony and Kaunayen chicken breeds. This article attempts to summarize the present status, distribution and attributes of livestock and poultry genetic resources of Manipur state.